Executive Development as an Instrument of Higher Control - Scott, William G. (Academy of Management Journal, 1963)
The article discusses the use of executive development as an instrument of organizational control. Development in this context refers to the planned influence of individual psychological processes. It is the purpose of this development to gain from employees attitudinal commitment to the philosophy, values, and goals of a business organization. A model for a planned program of influence is presented. The organizational learning facets of the plan include altering influences which affect employee attitudes, introducing employees to new values, and crystallization of new attitudes.